IMPLEMENTASI METODE ROLE PLAYING PEMILIHAN UMUM (PEMILU) DALAM MENINGKATKAN KEAKTIFAN BELAJAR - Ahmala, Majidatun (STIT Pemalang, 2024)
Abstract This study aims to find out more about the implementation of the role playing method in general elections (elections) in increasing the activeness of learning mathematics. The research method is qualitative descriptive. The research subjects in this study are 25 students IV MI Al-Akbar 1 Air Beetle. The data collection technique was carried out by observation of the role playing learning method for the General Election (Election). In addition, a description test was also carried out to obtain the final results of this study so that the improvement was known. Data analysis was carried out using descriptive data analysis by looking at the results of student learning activity by drawing conclusions. The results of the implementation of the role playing learning method applied by teachers at MI Al-Akbar 1 Air Kumbang class V are very satisfactory and in accordance with what is expected. This is proven by: 1) Fewer sleepy students in class 2) The number of students who actively ask questions about the material 3) The reduction of the monotonous classroom atmosphere because the method used is in accordance with the Mathematics subject, namely the role playing method, 4) Students become brave to express themselves. These activities help students get actively engaged, improve students' understanding of math concepts, and develop creative skills. As a result, students become more inspired and motivated in learning mathematics, as well as gain a deeper understanding of the relationship between mathematics and daily life.